Preservice Teachers’ Perceptions of C1 English Proficiency in a Chilean Teacher Education Program - Jessica Vega-Abarzúa; Marco Morales; Constanza Olivo; Francisca Rubilar; Eduardo Gutiérrez-Turner (Profile Issues in Teachers' Professional Development)
This mixed-methods study examined preservice teachers’ perceptions of C1 English proficiency, focusing on their linguistic competence, understanding, attitudes, and challenges. Conducted at a university in Ñuble, Chile, with 13 participants, data were gathered through a closed-ended questionnaire and a semi-structured interview. Findings suggest that perceived linguistic competence improves as students advance academically. Although participants’ understanding of the C1 level was often fragmented, they acknowledged the difficulty of achieving it and the importance of mastering grammar by graduation. Despite challenges, participants held positive attitudes toward the C1 standard. These findings aim to help teacher education programs better support preservice teachers’ progress toward C1 proficiency.